Amantadine Alleviates Postoperative Cognitive Dysfunction Possibly by Preserving Neurotrophic Factor Expression and Dendritic Arborization in the Hippocampus of Old Rodents - Zhong, Jing; Li, Jun; Ni, Cheng; Zuo, Zhiyi (Frontiers in Aging Neuroscience, 2020)
Objectives: Amantadine has been shown to attenuate postoperative learning and memory dysfunction in young adult rats. However, postoperative cognitive dysfunction often occurs in elderly patients. We aimed to determine whether amantadine attenuated postoperative learning and memory dysfunction and whether these effects were associated with improved dendritic arborization in old rodents. Methods: Eighteen-month old male C57BL/6J mice or Fischer 344 rats were subjected to right carotid artery exposure (surgery) under isoflurane anesthesia. This age represents an early old stage in rodents. Carotid artery exposure was used to simulate commonly performed carotid endarterectomy in elderly patients. Amantadine was injected intraperitoneally at 25 μg/g once a day for three days with the first dose at 15 min before surgery. The animalsy were tested by Barnes maze and fear conditioning starting one week after the surgery. Hippocampus was harvested for Western blotting and Golgi staining. Results: Surgery and anesthesia impaired the learning and memory in old mice and rats. Surgery reduced the expression of brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF), dendritic arborization and spine density in the hippocampus of old rats. These effects were attenuated by amantadine. The effects of amantadine were blocked by intracerebroventricular injection of anti-BDNF antibody or anti-GDNF antibody. Conclusion: Surgery and anesthesia impaired learning, memory and dendritic arborization in old rodents that are age relevant to postoperative cognitive dysfunction. These effects may be attenuated by amantadine via preserving the expression of neurotrophic factors.